Correlation of Knowledge and Compliance of Implementing 5m Health Protocols in the Post-Covid-19 Pandemic Period - Dahlia Arief Rantauni; Ellyzabeth Sukmawati (Institute of Computer Science (IOCS), 2022)
Background : In 2019, Coronavirus-19 (COVID-19) disease spread very rapidly and caused high mortality rate. It makes the government set the large-scale social restrictions (PSBB) and run the 5M health protocol aimed at preventing and reducing transmission of the COVID-19 virus. In order to prevent transmission, people are suggested to keep their distance, wash their hands, wear masks, reduce mobility, and stay away from crowds. Objective: this study aims to determine the relationship between COVID-19 knowledge level and compliance with health protocols. Methods: This study uses analytical research design through the distribution of questionnaires to respondents. Results : research of 76 respondents showed good knowledge, such as 67 respondents (88,2%), good attitude as much as 65 respondents (85,5%), good behavior 73 respondents (96,1%) with the average age of respondents of 20 (65,8%). Thus, obtained the relationship between knowledge and attitude (P value 0,01 ; RR 1,64); the relationship between knowledge and behavior (P value 0,47;RR 1,57); there is no relationship between attitude and behavior (P value 0,221 ; RR 1,39). Conclusion : There is a relationship between knowledge and attitude, knowledge and behavior, but there is no relationship between attitude and behavior. It is recommended that STIKES Serulingmas students could further increase awareness and knowledge related to COVID-19. Besides, it can be implemented in behavioral attitudes of compliance with implementing 5M health protocols in daily life.